Circulating tumour DNA sequencing to determine therapeutic response and identify tumour heterogeneity in patients with paediatric solid tumours. (February 2022) - Stankunaite, Reda; George, Sally L.; Gallagher, Lewis; Jamal, Sabri; Shaikh, Ridwan; Yuan, Lina; Hughes, Debbie; Proszek, Paula Z.; Carter, Paul; Pietka, Grzegorz; Heide, Timon; James, Chela; et al.
Abstract: Objective: Clinical diagnostic sequencing of circulating tumour DNA (ctDNA) is well advanced for adult patients, but application to paediatric cancer patients lags behind. Methods: To address this, we have developed a clinically relevant (67 gene) NGS capture panel and accompanying workflow that enables sensitive and reliable detection of low-frequency genetic variants in cell-free DNA (cfDNA) from children with solid tumours. We combined gene panel sequencing with low pass whole-genome sequencing of the same library to inform on genome-wide copy number changes in the blood. Results: Analytical validity was evaluated using control materials, and the method was found to be highly sensitive (0.96 for SNVs and 0.97 for INDEL), specific (0.82 for SNVs and 0.978 for INDEL), repeatable (>0.93 [95% CI: 0.89–0.95]) and reproducible (>0.87 [95% CI: 0.87–0.95]). Potential for clinical application was demonstrated in 39 childhood cancer patients with a spectrum of solid tumours in which the single nucleotide variants expected from tumour sequencing were detected in cfDNA in 94.4% (17/18) of cases with active extracranial disease. In 13 patients, where serial samples were available, we show a close correlation between events detected in cfDNA and treatment response, demonstrate that cfDNA analysis could be a useful tool to monitor disease progression, and show cfDNA sequencing has the potential to identify targetable variants that were not detected in tumour samples. Conclusions: This is the first pan-cancer DNA sequencing panel that we know to be optimised for cfDNA in children for blood-based molecular diagnostics in paediatric solid tumours. Graphical abstract: Image 1 Highlights: Developed a pan-paediatric solid tumour NGS capture panel for cfDNA profiling. Method validated to clinical reporting standards. Simultaneous Copy Number Variation detection by low-pass WGS. Correlation between ctDNA detection and treatment response. ctDNA sequencing may identify additional targetable variants.